2018
DOI: 10.1371/journal.pone.0198659
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA expression signature of CD4+ T cells in the transition of brucellosis into chronicity

Abstract: Brucellosis is a serious infectious disease that continues to be a significant cause of morbidity worldwide and across all ages. Despite early diagnosis and treatment, 10–30% of patients develop chronic brucellosis. Although there have been recent advances in our knowledge of Brucella virulence factors and hosts’ immune response to the infection, there is a lack of clear data regarding how the infection bypasses the immune system and becomes chronic. The present study investigated immunological factors and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…Additionally, miR-4649-3p was suggested to be a biomarker that can predict the transition to chronic disease in patients with brucellosis. 21 In the current study, the plasma miR-4649-3p level was significantly higher in psoriatic patients compared to the control group (p = 0.000, fc: 2.99). Increased expression of miR-4649-3p in psoriasis may lead to a decrease in Treg cell production (by suppressing FOXP3 gene) causing an exacerbation of immune response.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Additionally, miR-4649-3p was suggested to be a biomarker that can predict the transition to chronic disease in patients with brucellosis. 21 In the current study, the plasma miR-4649-3p level was significantly higher in psoriatic patients compared to the control group (p = 0.000, fc: 2.99). Increased expression of miR-4649-3p in psoriasis may lead to a decrease in Treg cell production (by suppressing FOXP3 gene) causing an exacerbation of immune response.…”
Section: Discussionsupporting
confidence: 44%
“…miR-4649-3p, is thought to be effective on Treg cells. Although miR-4649-3p has been implicated in different diseases, it has not been studied in the context of psoriasis [20,21]. miR-4649-3p was suggested to inhibit cell proliferation in nasopharyngeal carcinoma by targeting protein tyrosine phosphatase SHP-1 [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that the expression of miRNAs is significantly altered in RAW264.7 macrophage cells ( 42 ), CD4+ T cells ( 43 ), and CD8+ T cells ( 44 ) upon Brucella infection. We found that Gm28309 was primarily localized in the cytoplasm, suggesting a role as a miRNA sponge.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is much less information regarding miRNA in the context of Brucella infection [ 47 49 ]. Budak et al investigated the miRNA expression patterns in CD4+ and CD8+ T cells from patients, and reported discrete changes with acute vs. chronic brucellosis [ 50 , 51 ]. Another study reported the up-regulation of miR-1981 in RAW264.7 infected macrophages and showed the interaction of that microRNA with the 3’-UTR of Bcl-2, an apoptosis regulator [ 52 ].…”
Section: Discussionmentioning
confidence: 99%